Impact of thearubigins on the estimation of total dietary flavonoids in the European Prospective Investigation into Cancer and Nutrition (EPIC) study. - Zamora-Ros, R; Knaze, V; Romieu, I; Scalbert, A; Slimani, N; Clavel-Chapelon, F; Touillaud, M; Perquier, F; Skeie, G; Engeset, D; Weiderpass, E; Johansson, I; et al. (2013)
Thearubigins (TR) are polymeric flavanol-derived compounds formed during the fermentation of tea leaves. Comprising ∼70% of total polyphenols in black tea, TR may contribute majorly to its beneficial effects on health. To date, there is no appropriate food composition data on TR, although several studies have used data from the US Department of Agriculture (USDA) database to estimate TR intakes. We aimed to estimate dietary TR in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort and assess the impact of including TR or not in the calculation of the total dietary flavonoid intake. Dietary data were collected using a single standardized 24-h dietary recall interviewer-administered to 36 037 subjects aged 35-74 years. TR intakes were calculated using the USDA database. TR intakes ranged from 0.9 mg/day in men from Navarra and San Sebastian in Spain to 532.5 mg/day in men from UK general population. TR contributed <5% to the total flavonoid intake in Greece, Spain and Italy, whereas in the UK general population, TR comprised 48% of the total flavonoids. High heterogeneity in TR intake across the EPIC countries was observed. This study shows that total flavonoid intake may be greatly influenced by TR, particularly in high black tea-consuming countries. Further research on identification and quantification of TR is needed to get more accurate dietary TR estimations.